(untitled) (European Journal of Pure and Applied Mathematics, 2026)
This study focuses on unifying theories of bipolar intuitionistic fuzzy sets in the field of BCK-algebras, leading to the development of a new framework for bipolar intuitionistic fuzzy ideals in BCK-algebras. The article introduces the concepts of bipolar intuitionistic fuzzy subalgebras and bipolar intuitionistic fuzzy ideals in BCK-algebras, with illustrative examples. Subsequently, we investigate various related characteristics. We also provide conditions under which a bipolar intuitionistic fuzzy set is considered a bipolar intuitionistic fuzzy ideal.